Effects of eight-week resistance and complex training on the biomechanical characteristics of lower limbs during badminton backhand forward lunge - Xie, Zhonghao; Wu, Xingyu; Liang, Huiting; Li, Wei; Li, Renjie; Wang, Zhe; Wen, Tao; Huang, Zhiguan (Frontiers in Sports and Active Living, 2025)
ObjectivesThis study aimed to examine the effects of an 8-week resistance training (RT) or complex training (CT) program on lower limb biomechanical characteristics during the backhand forward lunge in male amateur badminton players.MethodsTwenty male amateur badminton players were randomly assigned to either a complex training group or a resistance training group for an eight-week intervention. Lower limb kinematics and dynamics were captured before and after the intervention using an eight-camera Vicon motion system and two AMTI force plates. The measured variables included phase time, joint angles, joint range of motion (ROM), and joint moments during the stance phase. Discrete variables were analyzed using Generalized Estimating Equations (GEE), while continuous variables were evaluated using Statistical Parametric Mapping 1D (SPM1D).ResultsThe RT group significantly reduced recovery phase time (0.3 vs. 0.28 s, p < 0.01) and increased ankle transverse plane ROM (16.83° vs. 20.61°, p = 0.005), along with improvements in hip and knee flexion angles and ankle plantarflexion angle. The CT group significantly reduced both braking phase time (0.32 vs. 0.28 s, p = 0.002) and recovery phase time (0.31 vs. 0.28 s, p < 0.01), as well as decreased knee sagittal ROM (83.30° vs. 78.84°, p = 0.04).ConclusionBoth training interventions enhanced the performance of the backhand forward lunge. Complex training resulted in greater improvements in execution efficiency, while resistance training not only improved efficiency but also demonstrated potential for reducing knee and ankle injury risk.